Variability in the Northern North Atlantic and Arctic Oceans Across the Last Two Millennia: A Review. Issue 8 (24th August 2019) - Moffa‐Sánchez, P.; Moreno‐Chamarro, E.; Reynolds, D. J.; Ortega, P.; Cunningham, L.; Swingedouw, D.; Amrhein, D. E.; Halfar, J.; Jonkers, L.; Jungclaus, J. H.; Perner, K.; Wanamaker, A.; et al.
Abstract: The climate of the last two millennia was characterized by decadal to multicentennial variations, which were recorded in terrestrial records and had important societal impacts. The cause of these climatic events is still under debate, but changes in the North Atlantic circulation have often been proposed to play an important role. In this review we compile available high‐resolution paleoceanographic data sets from the northern North Atlantic and Nordic Seas. The records are grouped into regions related to modern ocean conditions, and their variability is discussed. We additionally discuss our current knowledge from modeling studies, with a specific focus on the dynamical changes that are not well inferred from the proxy records. An illustration is provided through the analysis of two climate model ensembles and an individual simulation of the last millennium. This review thereby provides an up‐to‐date paleoperspective on the North Atlantic multidecadal to multicentennial ocean variability across the last two millennia. Key Points: Review of the progress made to date on the study of variability in the northern North Atlantic and Arctic Oceans in the last two millennia Synthesis of the advancements in high‐resolution marine proxies and climate models and compare them both